2019
DOI: 10.1136/sextrans-2019-054163
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of syphilis among HIV-infected men in Singapore, 2006–2017: temporal trends and associated risk factors

Abstract: ObjectiveThere have been recent reports globally on substantial increase in syphilis diagnoses particularly among high-risk men. The aim of this study was to assess temporal trends of incident syphilis and associated risk factors among HIV-infected men in Singapore.MethodsWe conducted retrospective cohort analysis using the clinical database maintained by the Clinical HIV Programme at the National Centre for Infectious Diseases, Singapore. HIV-infected men with a negative syphilis result at baseline who had un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
2
7
2
Order By: Relevance
“…Studies in some countries have shown a higher syphilis infection among MSM associated with higher frequency of condomless anal intercourse, younger age, and number of sex partners. 7,14,22 In contrast, our study showed no association between age and incident syphilis infection. This finding is similar to studies in Peru and Shenzhen, 23,24 but differs from finding reported in China, Tokyo and Singapore and other Asian countries that reported more syphilis infection in younger age.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Studies in some countries have shown a higher syphilis infection among MSM associated with higher frequency of condomless anal intercourse, younger age, and number of sex partners. 7,14,22 In contrast, our study showed no association between age and incident syphilis infection. This finding is similar to studies in Peru and Shenzhen, 23,24 but differs from finding reported in China, Tokyo and Singapore and other Asian countries that reported more syphilis infection in younger age.…”
Section: Discussioncontrasting
confidence: 96%
“…6 Our incidence rate is lower than reported from Singapore in 2017 incidence among MSM was 26.04 (19.97–33.40 per 100 PYFU. 7 Our findings are similar to a meta-analysis which reported incidence rates ranging from 1.8 to 14.9 per 100 PYFU. 12…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The increase in HCV incidence coincided with the rising trend in the incidence of syphilis infection among HIV-infected men who had ever sought HIV care at the largest referral centre in Singapore. 35 In the Swiss HIV cohort study, the significant increase in syphilis acquisition among MSM mirrored that of HCV infection incidence. 15,36 In the United States, Western Europe, Australia and China, recent upsurges of syphilis infections have also been reported, particularly among highrisk groups such as gay, bisexual and other MSM.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the difference has not been established. One of the reasons for the difference is that HIV-infected heterosexual patients have been infected for longer period of time, therefore they might have been treated; while the MSM, on the other hand, has recently been infected with HIV and thus they might have just currently been diagnosed (Ang et al, 2020;Roth et al, 2020). Ang et al also confirmed that the annual incidence rate of syphilis was consistently higher among MSM than in heterosexual men and the incidence was on the rise especially in MSM group with the risk factors including younger age, race, and being an MSM.…”
Section: Discussionmentioning
confidence: 99%